Teacher Experience of Guidance and Counseling in Treating Youth with Cyberbullying Case - Rinjani, Santi; Suryani, Suryani; Sriati, Aat; Nugraha, Andri (Universitas Muhammadiyah Yogyakarta, 2023)
Background: Cyberbullying in adolescents may cause depression, decreased academic achievement, withdrawal from the environment, family and the presence of suicidal ideation. The success of teachers in dealing with cyberbullying is unknown.Objective: To explore the Guidance and Counseling Teachers experience in dealing with adolescents with cyberbullying incidents.Methods: This study used a qualitative descriptive approach with a phenomenological approach and data were collected through in-depth interviews with 8 Guidance and Counseling Teachers who deal with adolescents with cyberbullying incidents. Data analysis in this study used the Colaizzi method.Results: In this study, there were five essential themes in this research including cyberbullying is not a serious problem, various problems faced in dealing with cyberbullying, emotional responses to cyberbullying victims, cyberbullying victims are weak emotional mentality students and lack of coordination between parents, teachers subjects and Guidance and Counseling teachers.Conclusion: The problem of cyberbullying has considered as unserious problem and there is a lack of coordination between parents, subject teachers and guidance and counseling teachers. So that special training is needed to deal with cyberbullying, there are guidelines, clear cyberbullying prevention strategies and the existence of government agencies that specifically handle cyberbullying case.